Penerapan informasi akuntansi diferensial dalam pengambilan keputusan manajemen pada UMKM Gilingan Padi Mekar Sari Desa Kosio Kecamatan Dumoga Tengah - Pinontoan, Regina Firelsa; Pangemanan, Sifrid Sonny; Runtu, Treesje (Universitas Sam Ratulangi, 2020)
Differential accounting information is one of the information needed by the management of a company in planning and decision making, especially accept or reject for special orders, which will help management in this case UMKM Gilingan Padi Mekar Sari which often get special orders. The purpose of this study was to determine the application of differential accounting information in the decision to accept or reject special orders to produce superwin rice and ciherang rice types at UMKM Gilingan Padi Mekar Sari. The method used in this research is descriptive qualitative. The results of this study can be seen based on the comparative calculation of regular production and special order production using the differential accounting information of the UMKM Gilingan Padi Mekar Sari in receiving special orders for both products namely superwin rice and ciherang rice will get an additional total differential profit of Rp 43.441.500. Therefore, the use of differential accounting information is needed in the decision to accept or reject special orders.